Using Administrative Data to Assess the Impact and Sustainability of Rwanda's Land Tenure Regularization - Ali, Daniel Ayalew (World Bank E-Library Archive, 2016)
Rwanda's completion, in 2012/13, of a land tenure regularization program covering the entire country allows the use of administrative data to describe initial performance and combine the data with household surveys to quantify to what extent and why subsequent transfers remain informal, and how to address this. In 2014/15, annual volumes of registered sales ranged between 5.6 percent for residential land in Kigali and 0.1 percent for agricultural land in the rest of the country; and US